Combined oral contraceptives promote androgen receptor and oestrogen receptor alpha upregulation in the female prostate (Skene's paraurethral glands) of adult gerbils (Meriones unguiculatus) - Pinto, Eliana G.; Campos, Mônica S. [UNESP]; Falleiros-Júnior, Luiz R. [UNESP]; Marques, Mara R.; Taboga, Sebastião R. [UNESP]; Castro, Carlos H.; Biancardi, Manoel F.; Santos, Fernanda C. A. (CSIRO Publishing, 2018)
The aim of this study was to evaluate the effects of cyproterone acetate (CPA) and ethinyloestradiol (EE) alone or in combination on the female prostate of adult gerbils. Adult females were exposed for 21 days to daily oral doses of CPA (1 mg kg-1), EE (10 g kg-1) or a combination of CPA and EE. Female prostatic complexes were removed, weighed and subjected to morphological, stereological, immunohistochemical and ultrastructural analyses. CPA treatment caused epithelial atrophy and decreased prostate secretory activity. The EE treatment group showed glandular hyperplasia, a high cell-proliferation index and an increase in androgen and oestrogen receptor α (AR and ERα) immunoreactivity. Combined treatment (CPA+EE) caused adverse effects, such as an increase in cell proliferation, higher AR and ERα immunoreactivity, prostatic intraepithelial neoplasia, cell degeneration and aging. In conclusion, the CPA-only treatment promoted antiandrogenic effects on the female gerbil prostate, whereas EE-only had a potent oestrogenic activity. However, when combined, EE overlapped the effects of CPA, changing the pattern of glandular hormonal regulation and stimulating the development of prostatic lesions in female gerbils.
Keywords: hormone receptor; morphology; progestin; reproduction; vagina